The durability and rehabilitation technologies of concrete sewerage pipes: A state-of-the-art review - Zhuge, Yan; Fan, Wei; Duan, Weiwei; Liu, Yue (Journal of Asian Concrete Federation, 2021)
This paper reviews the literature available on the subject of the durability of concrete sewer pipes and the corresponding rehabilitation technologies. An introduction related to the importance of the sewer system in urban life and its durability issues was first discussed as most people did not recognise the scale and complexity of the underground sewer system. Then the recent development of alternative binder materials or filler materials to improve the acid resistance of concrete was specified. For instance, the effects of alternative binders on the hydration products and the mechanism of biogenic corrosion were discussed in detail. The paper ends with the current rehabilitation technologies and the structural performance of rehabilitated sewer pipes. Also, some suggestions associated with future research were made.